2010
DOI: 10.1111/j.1742-7924.2010.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a problem‐solving counseling program to facilitate intensified walking on Koreans with type 2 diabetes

Abstract: Aim: This study aimed to evaluate the immediate and long-term effects of a 12 week problem-solving (PS) counseling program to facilitate intensified walking with machinery monitoring on persons with type 2 diabetes mellitus in Korea. Methods:The study used a quasi-experimental design. The participants were 57 patients with diabetes from three endocrinology or internal medicine clinics in an urban city of South Korea. Moderate-intensity walking and PS counseling were recommended to both groups. The difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…The 24 intervention studies applied the following research designs: randomized controlled trial (n = 17) [7-23] and quasi-experimental or preintervention/postintervention design (n = 8) [24-32]. …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 24 intervention studies applied the following research designs: randomized controlled trial (n = 17) [7-23] and quasi-experimental or preintervention/postintervention design (n = 8) [24-32]. …”
Section: Resultsmentioning
confidence: 99%
“…Race/ethnicity of study participants was not reported in 3 (13%) studies [18,22,31]. One study examined Caucasians [32], 12 (50%) studies included multiple ethnicities (generally Caucasian, African American, and Latino)[7,11,12,14-16,19,21,23,25,26,30], 5 (21%) studies were African American only [8,9,20,27,28], 2 study samples were Latino[13,17], and 1 study sample was South Korean [24]. …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations